Photo-Thermal Conversion Properties of Selective Coatings with Aluminium and Nickel Powders Additives - Ryadh, Mustafa Ashoor; Al-Tabbakh, Ahmed A. (Iraqi Journal of Science, 2026)
Efficient solar energy harvesting through selective absorber coatings is critical for advancing sustainable thermal applications, such as domestic hot water production and water purification. Enhancing photo-thermal conversion while maintaining durability and ease of fabrication remains a challenge. To address this, a composite selective coating was developed by decorating a heat-resistant paint with aluminium and nickel particles, applied via air-spraying on the base paint layer. The coatings were characterized structurally, morphologically, and compositionally using optical microscopy, field-emission electron microscopy, UV-Vis spectroscopy, energy dispersive X-ray analysis, and elemental mapping. Photo-thermal conversion performance was evaluated by measuring solar absorbance and the maximum substrate temperature under solar irradiation using a flat-plate collector setup. The study correlates the photo-thermal conversion with the coatings’ structural and compositional features. Notably, the coating decorated with nickel particles achieved a maximum solar absorbance of 96.07%, enabling substrate temperatures exceeding the boiling point of water without the need for antireflection coatings. The fabrication method and superior photo-thermal properties position this composite coating as a promising candidate for domestic hot water generation and water purification applications, outperforming conventional selective coatings regardless of collector geometry.